The Impact of labor Turnover on The Service Quality of Hotels - Saleh, Motasem; Kabalan, H. (International Journal of Engineering and Management Sciences, 2020)
This study aimed to know the dimensions of labor turnover (low morale, poor employees training, payment, job satisfaction) and study the effect of these dimensions on the quality of service in hotels. The results of multiple regression show that there is an effect of dimensions labor turnover on quality of service. Correlation between labor turnover and tangibility was the strongest and there is a moderate relationship between labor turnover and each of responsibility, reliability, assurance, and empathy.